Use of technological resources in Education: paths and perspectives (Research, Society and Development, 2020)
The relationship between technology and education is still a very controversial topic and involves different positions and arguments. It appears that many schools prohibit the use of cell phones, smartphones, tablets, laptops and the like in the classroom, a prohibition considered inappropriate by a large portion of students. However, among teachers there is a clear division of positioning, as some advocate the use of these resources and even seek to expand their possibilities of application in educational environments, while others believe that these technologies tend to take the student's concentration, impairing their learning. Given this scenario, this work aims to make considerations about Information and Communication Technologies in the educational context, with the objective of offering answers to some questions such as, How technology can be an ally of Education in the teaching and learning processes? In what contexts and situations should these resources be used in the classroom? To this end, we seek support in publications by some theorists in the field in order to analyze possible contributions and problems related to the use of technological resources in Education that can generate advances in the daily lives of teachers and students, favoring the formative process desired in school spaces.